Ayurvedic Management of Labour (Prasava) with Sthanika Chikitsa - Yallavva N Midachakkanavar; Shreyes; Sujatha S Patil; I B Kotturshetti (AYUSHDHARA, 2025)
Ayurveda Acharyas have dedicated a branch called Prasuti and Stree roga which is branch among the Astangas of Ayurveda that is dedicated for the health and well-being of the women. Acharyas have described in detail about the monthly regimen or the Masanumasika Garbhini Paricharya that needs to be followed by the pregnant women for the healthy baby and also for her optimum health. Prasava or the labour is also described in detail with stepwise management of each stage of labour. Sthanika Chikitsa are the unique local therapies mentioned in Ayurvedic science indicated for the management of Yonivyapadas or the genital disorders, Yonirogas and also in Sukhaprasava. These include Yonipichu, Yonikalka, Yonilepa Yonidhawan, Yoniparisheka, Ksharakarma, Yonipinda, Yonivarti, Yonidhoopan, Uttarabasti etc procedures. For this Sukha Prasava, many treatments and the interventions have been described by the Ayurveda Acharyas among which the Sthanika chikitsa has a pivotal role. Sthanika Chikitsa is also important as Sarvdehika Chikitsa. In these local therapies, if the drugs are administered with proper method and indications, it acts on the target organ and provides the better and significant results compared to the internal medications. Present study details of these therapies and its application in the management of labour or the Sukha Prasava as described according to Ayurveda.